SUPERIORITAS LAKI-LAKI DALAM DUNAI SUFI: Tinjauan Budaya Islam Dalam Praktek Kepemimpinan Spiritual - Abdurrohmat, Abdurrohmat (EL HARAKAH Jurnal Budaya Islam, 2008)
Substantially, the spiritual teaching of Sufism is not represented and represents one of gender group, male or female. The Sufism spiritual teaching has great universal scope for male and female. In the empirical domain, in fact, the spiritual teaching still conducts patrimonial culture behavior which makes the original Sufism spiritual teaching endangered to fail. This situation also happened in the leadership on the practices of mysticism teaching culture which has been dominated by the males. As a consequence, the female will never get the chance to lead the teaching practice. The situation encourages the writer to dig up the imbalance issues in the male and female role in the Sufism teaching practices. The article raises the questions whether the spiritual teacher should be the male and why the leadership capacity of the spiritual teaching has been dominated by the male. Furthermore, the exploration will be a helpful resource to have better understanding on the Sufism teaching practice.Â Secara substansi, ajaran spiritual tasawuf tidak terwakili dan mewakili salah satu kelompok gender, laki-laki atau perempuan. Ajaran spiritual Sufisme memiliki cakupan universal yang besar untuk pria dan wanita. Dalam ranah empiris, sebenarnya, pengajaran spiritual masih melakukan perilaku budaya patrimonial yang membuat ajaran spiritual Sufisme asli terancam gagal. Keadaan ini juga terjadi pada kepemimpinan praktik budaya ajaran mistisisme yang telah didominasi oleh laki-laki. Sebagai konsekuensinya, perempuan tidak akan pernah mendapatkan kesempatan untuk memimpin praktik mengajar. Situasi mendorong penulis untuk menggali masalah ketidakseimbangan peran pria dan wanita dalam praktik pengajaran tasawuf. Artikel tersebut mengangkat pertanyaan apakah guru spiritual seharusnya laki-laki dan mengapa kapasitas kepemimpinan ajaran spiritual didominasi oleh laki-laki. Selanjutnya, eksplorasi akan menjadi sumber yang bermanfaat untuk memiliki pemahaman yang lebih baik mengenai praktik pengajaran tasawuf.